Asia’s Strategic Role in Global Supply Chain Resilience: Insights for Inclusive Global IR Frameworks Amid the Russia–Ukraine Conflict - Kunkunrat (NAJAHA, 2025)
This study is motivated by the dominance of Western narratives in analysing the impact of the Russia–Ukraine war on global supply chains, which often overlooks the strategic role of Asian countries in maintaining economic stability. The purpose of this research is to examine Asia's contributions to global supply chain resilience and to assess how Global International Relations (IR) frameworks can incorporate Asian perspectives for a more balanced understanding. Employing a qualitative descriptive approach, primary data were collected through semi-structured interviews with international relations experts, industry practitioners, and economic analysts, alongside observations of regional and global policy forums such as APEC and the World Economic Forum on Asia. In contrast, secondary data were obtained from academic journals, international reports, and current news sources. The findings indicate that Asian states have strategically mitigated disruptions by diversifying energy and material sources, coordinating regionally on food security, and participating in multilateral platforms, demonstrating pragmatism and strategic autonomy while contributing to SDG 8 (Decent Work & Economic Growth), SDG 9 (Industry, Innovation & Infrastructure), SDG 12 (Responsible Consumption & Production), and SDG 17 (Partnerships for the Goals). The study concludes that Asia acts as a normative actor in Global IR, balancing economic interests, national sovereignty, and multilateral cooperation. Limitations include a focus on major Asian economies and ASEAN, potential subjectivity in interviews, and limited access to strategic documents. Nevertheless, the research offers practical implications for policymakers and international organisations by highlighting Asia's proactive role in fostering resilient, inclusive supply chains. It presents original value by challenging Western-centric assumptions, providing updated empirical evidence of non-Western approaches to global economic governance.